Next-Generation Sequencing Accelerates Crop Gene Discovery. (March 2019) - Nguyen, Khanh Le; Grondin, Alexandre; Courtois, Brigitte; Gantet, Pascal
Abstract : The identification and isolation of genes underlying quantitative trait loci (QTLs) associated with agronomic traits in crops have been recently accelerated thanks to next-generation sequencing (NGS)-based technologies combined with plant genetics. With NGS, various revisited genetic approaches, which benefited from higher marker density, have been elaborated. These approaches improved resolution in QTL position and assisted in determining functional causative variations in genes. Examples of QTLs/genes associated with agronomic traits in crops and identified using different strategies based on whole-genome sequencing (WGS)/whole-genome resequencing (WGR) or RNA-seq are presented and discussed in this review. More specifically, we summarize and illustrate how NGS boosted bulk-segregant analysis (BSA), expression profiling, and the construction of polymorphism databases to facilitate the detection of QTLs and causative genes. Highlights: The swift development of next-generation sequencing (NGS) has accelerated quantitative trait locus (QTL) mapping and gene discovery in crops. High-throughput NGS-based genotyping platforms provide an extensive capacity to develop comprehensive polymorphism datasets including SNPs, InDels, structural variations, and genomic rearrangement. Whole-genome resequencing combined with bulk-segregant analysis offers a high density of informative SNPs, helping to detect QTLs without genotyping the entire mapping population. However, phenotyping of the entire population is still required. RNA-seq is useful to simultaneously genotype and phenotype segregating populations, releasing genomic information on mRNA and expression levels. Polymorphism databases generated by whole-genome sequencing using large-accession collections constitute new shared resources that facilitate QTL detection and gene discovery.